2022
DOI: 10.1016/j.redox.2022.102246
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-9 facilitates liver regeneration following hepatectomy

Abstract: Aquaporin-9 (AQP9) is an aquaglyceroporin strongly expressed in the basolateral membrane of hepatocytes facing the sinusoids. AQP9 is permeable to hydrogen peroxide (H 2 O 2 ) and glycerol as well as to water. Here, we report impaired liver regeneration in AQP9 −/− mice which involves altered steady-state H 2 O 2 concentration and glucose metabolism in hepatocytes. AQP9 −/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…AQP9 is permeable to H 2 O 2 , as well as glycerol and water, beneficial in liver regeneration. Impaired H 2 O 2 transport across plasma membranes of cultured AQP9 −/− hepatocytes resulted in H 2 O 2 accumulation and oxidative injury, whereas overexpression of AQP9 or AQP3 in AQP9 −/− mice fully rescued liver regeneration, oxidative protection and glucose metabolism [ 97 ]. Up-regulation of various AQP classes in inflammatory conditions is essential for immune cell migration and viability [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…AQP9 is permeable to H 2 O 2 , as well as glycerol and water, beneficial in liver regeneration. Impaired H 2 O 2 transport across plasma membranes of cultured AQP9 −/− hepatocytes resulted in H 2 O 2 accumulation and oxidative injury, whereas overexpression of AQP9 or AQP3 in AQP9 −/− mice fully rescued liver regeneration, oxidative protection and glucose metabolism [ 97 ]. Up-regulation of various AQP classes in inflammatory conditions is essential for immune cell migration and viability [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were sacrificed for serum and liver tissue collection. In addition, primary cultured hepatocytes were collected from mice according to a previous reference 25 . The TG content was measured by a biochemical assay kit (Boyao, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…found that when PI3K-AKT and insulin signaling pathways were suppressed, autophagy was inhibited, apoptosis was enhanced, proliferation was impaired, and cell death was promoted in hepatocytes of aquaporin-9 knockout mice. 154 Lin et al. revealed that translation control tumor protein (TCTP) promoted LR in mice by activating PI3K/AKT signaling pathway through interaction with mTORC2.…”
Section: Signaling Pathways In Lrmentioning
confidence: 99%
“… Zhang et al. 154 TCTP promoted LR in mice by activating PI3K/AKT signaling pathway through interaction with mTORC2. Lin et al.…”
Section: Signaling Pathways In Lrmentioning
confidence: 99%